Strategi Pembelajran Diferensiasi Pada Pembelajaran PAI Siswa Kelas X Berdasarkan Kurikulum Merdeka - Sholiha, Mar’atus; Marzuki, Ahmad; Muhtarom, H. Ali; M. Jamhuri (STAI Ihyaul Ulum Gresik, 2024)
The number of grade X students at Darut Taqwa High School is less active in participating in Islamic Religious Education learning due to the less than optimal learning model. Which in this case can be overcome by applying differentiation learning as a learning model that prioritizes student interests in terms of student learning interests and what students like which can make the class more active during the learning process. The research focus referred to by the researcher is 1) strategies applied in differentiation learning in Islamic Religious Education learning in class X, 2) obstacles faced by Islamic Religious Education teachers in implementing differentiation learning. The purpose of this study was to determine the strategies carried out in the application of differentiation learning in grade X students of SMA Darut Taqwa Purwosari. And to find out what are the obstacles faced by Islamic Religious Education teachers in the application of differentiation learning in grade X students of Darut Taqwa Purwosari High School. The type of research used is Descriptive Qualitative research. The data and data sources used are secondary data and primary data. Data collection techniques used in the form of observation, interviews, and documentation. Technical data analysis with reduction, presentation of data, and conclusion making. From the results of the study, it was found that; 1) the strategy applied in differentiation learning is based on content differentiation (adultery chapter material), process (using problem solving learning model strategies by making pseudonym illustrations), and products (students are able and dare to tell the truth in the problems faced). And this differentiation learning is very effectively used as an evaluation material for Islamic Religious Education learning at Darut Taqwa Purwosari High School. 2) One of the differentiation learning obstacles faced by educators is that teachers must be able to know various characteristics of students, and must use a variety of varied learning resources. So it can be concluded that the application of differentiation learning can increase students' interest in learning Islamic Religious Education at SMA Darut Taqwa Purwosari class X.